NKG2D Signaling Leads to NK Cell Mediated Lysis of Childhood AML - Patrick Schlegel; Kerstin Ditthard; Peter Lang; Markus Mezger; Sebastian Michaelis; Rupert Handgretinger; Matthias Pfeiffer (Journal of Immunology Research)
Natural killer cells have been shown to be relevant in the recognition and lysis of acute myeloid leukemia. In childhood acute lymphoblastic leukemia, it was shown that HLA I expression and KIR receptor-ligand mismatch significantly impact ALL cytolysis. We characterized 14 different primary childhood AML blasts by flow cytometry including NKG2D ligands. Further HLA I typing of blasts was performed and HLA I on the AML blasts was quantified. In two healthy volunteer NK cell donors HLA I typing and KIR genotyping were done. Blasts with high NKG2D ligand expression had significantly higher lysis by isolated NK cells. Grouping the blasts by NKG2D ligand expression led to a significant inverse correlation of HLA I expression and cytolysis in NKG2D low blasts. Furthermore, a significant positive correlation of NKG2D ligand expression and blast cytolysis was shown. No impact of KIR ligand-ligand mismatch was found but a significantly increased lysis of homozygous C2 blasts by KIR2DL1 negative NK cells (donor B) was revealed. In conclusion, NKG2D signaling leads to NK cell mediated lysis of childhood AML despite high HLA I expression.